2020
DOI: 10.1111/ipd.12647
|View full text |Cite
|
Sign up to set email alerts
|

Digital occlusal analysis of vertical dimension and maximum intercuspal position after placement of stainless steel crown using hall technique in children

Abstract: Mastication provides the adequate stimulus for proper functioning and normal development of maxilla and mandible. Several factors potentially influence masticatory efficiency including occlusal contact area, number of functional teeth, and bite force. Areas of contact between occluding teeth determine the area available for shearing food during each chewing cycle. 1 Long-term mastication on one side due to gross destruction of untreated caries leads to asymmetric masticatory muscles or decrease in the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Other researchers have suggested similar results from their studies. Van der Zee 4 and Nair 5 indirectly measured the VDO by measuring the overbite depth and reported the equilibration of overbite 30 days after placing the Hall crown, suggesting that this study is generally consistent with these studies. This finding is important, as studies have suggested that the mechanism of the VDO recovery may have a more significant relationship with children's alveolar bone compensation 23 and movement of teeth.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Other researchers have suggested similar results from their studies. Van der Zee 4 and Nair 5 indirectly measured the VDO by measuring the overbite depth and reported the equilibration of overbite 30 days after placing the Hall crown, suggesting that this study is generally consistent with these studies. This finding is important, as studies have suggested that the mechanism of the VDO recovery may have a more significant relationship with children's alveolar bone compensation 23 and movement of teeth.…”
Section: Discussionsupporting
confidence: 82%
“…This system can be used in adults and in children at early childhood. 5 A previous study showed that in children with primary dentition, following the general trend, maximum occlusal bite force, electromyography, and jaw movement pattern increased gradually, yet not significantly. 17 Occlusal force is an indicator to reflect the state of masticatory function.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This difference may not be clinically significant if the patients are considered to be in mixed dentition, and during this period, physiological changes occur due to the development of the occlusion. Other studies have reported that with the placement of SSC with the Hall technique, the vertical dimension is re‐established in a period of four weeks 29,30 . This compensation may occur due to the intrusion of the restored molar and its antagonist, the eruption of other teeth, or the combination of both 28 .…”
Section: Discussionmentioning
confidence: 99%